Examining the Relationship of Some Performance Tests Applied to Young Soccer Players - Erkan Bütün; Gökhan Hadi; Bekir Mehtap; Veysel Böge (Selcuk University, 2023)
Soccer is a sport branch in which a wide range of movements of different intensities are applied, which includes long-term, rapidly changing runs as a game structure, and physical parameters such as strength, agility and endurance are kept in the foreground in addition to tactical and technical skills. At this point, it is aimed to examine the relationship between different performance tests applied in young soccer players in this study. 21 male soccer players (16,33± 0,66 years, height; 172,4± 6,05 cm, body weight: 57,00± 8,81 kg) from an amateur soccer team in Konya voluntarily participated in the study. In the study, anthropometric measurements, two legged vertical jump test, yo-yo intermittent recovery 1 and 2 test, 30m sprint test and agility t test parameters were measured. The data were analyzed using the SPSS 24 package program, and the Pearson Correlation method was used in the analysis of the obtained data. As a result of the analysis of the data; A negative correlation was found between two legged vertical jump data and 30m speed and agility t test. A positive and significant correlation was found with the 30m sprint test and the agility t test. And also, a significant negative correlation was found between agility t test and yo-yo intermittent recovery 1 and yo-yo intermittent recovery 2 tests. In addition, a significant positive correlation was observed between the yo-yo intermittent recovery 2 test and the yo-yo intermittent recovery 1 test. As a result, it has been observed that different performance tests applied in young soccer players in determining the basic motoric characteristics are both negatively and positively correlated with each other.